Analysis of Breast Care Factors for Increasing Breast Milk Production In Pagar Merbau Public Health Community Center, Medan - Zaim Anshari (Universitas Muhammadiyah Sumatera Utara, 2023)
Breastfeeding is the obligation of a mother to give milk to her baby after childbirth (post-partum). To provide the right quantity and quality of breast milk that requires a formal agreement, such as maintaining and caring for breasts. Breast care should start from the time of pregnancy during childbirth (puerperium). Several factors that need to consider in breast care are providing breast massage, maintaining breast hygiene, using a bra as a breast protector, and consuming nutrition. This study is a quasi-experimental study that aims to determine whether breast care can increase milk production in post-partum mothers. The results showed that offering massage to the breasts, maintaining breast hygiene, and consuming nutrition affected the production of breast milk in post-partum mothers. The use of a bra in post-partum mothers does not have a significant effect on increasing milk production in post-partum mothers.